The landscape of nutrition stakeholders in Odisha - Kohli, Neha; Pradhan, Mamata; Menon, Purnima (International Food Policy Research Institute, 2013)
Odisha has a diverse network of nutrition stakeholders, including government departments, donors, and nongovernment organizations. These stakeholders play a critical role in shaping the nutrition policy agenda, implementing nutrition actions on the ground, and funding nutrition interventions. To better understand the interactions among these stakeholders, their relative influence on program and policy decisions, and their perspectives on how to ensure robust and productive interactions among each other, a team from POSHAN conducted an exercise to map this network.